Turbidity composition and the relationship with microbial attachment and UV inactivation efficacy - Farrell, Charlotte; Hassard, Francis; Jefferson, Bruce; Léziart, Tangui; Nocker, Andreas; Javis, Peter (Elsevier, 2017)
Turbidity in water can be caused by a range of different turbidity causing materials (TCM). Here the characteristics and attachment of bacteria to TCMs was assessed and the resultant impact on UV disinfection determined. TCMs represent potential vehicles for bacterial penetration of water treatment barriers, contamination of potable supplies and impact on subsequent human health. The TCMs under investigation were representative of those that may be present in surface and ground waters, both from the source and formed in the treatment process. The TCMs were chalk, Fe (III) hydroxide precipitate, kaolin clay, manganese dioxide and humic acids, at different turbidity levels representative of source waters (0, 0.1, 0.2, 0.4, 1, 2, and 5 NTU). Escherichia coli and Enterococcus faecalis attachment followed the order of Fe(III) > chalk, with little to no attachment seen for MnO2, humic acids and clay. The attachment was postulated to be due to chalk and Fe(III) particles having a more neutral surface charge resulting in elevated aggregation with bacteria compared to other TCMs. The humic acids and Fe(III) were the TCMs which influenced inactivation of E. coli and E. faecalis due to decreasing UV transmittance (UVT) with increasing TCM concentration. The presence of the Fe(III) TCM at 0.2 NTU resulted in the poorest E. coli inactivation, with 2.5 log10 reduction at UV dose of 10 mJ cm− 2 (kd of − 0.23 cm2 mJ− 1) compared to a 3.9 log10 reduction in the absence of TCMs. E. faecalis had a greater resistance to UV irradiation than E. coli for all TCMs. Effective disinfection of drinking water is a priority for ensuring high public health standards. Uniform regulations for turbidity levels for waters pre-disinfection by UV light set by regulators may not always be appropriate and efficacy is dependent on the type, as well as the amount, of turbidity present in the water.
Keywords: Water quality; UV disinfection; Inactivation; Faecal indicator organism; Turbidity; E. coli; E. faecalis